Service Orientation in Holonic and Multi-Agent Manufacturing Proceedings of SOHOMA 2018 - Borangiu, Theodor; Trentesaux, Damien; Thomas, André; Cavalieri, Sergio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the peer-reviewed papers presented at the 8th edition of the International Workshop "Service Orientation in Holonic and Multi-Agent Manufacturing - SOHOMA'18" held at the University of Bergamo, Italy on June 11-12, 2018. The objective of the SOHOMA annual workshops is to foster innovation in smart and sustainable manufacturing and logistics systems by promoting new concepts, methods and solutions that use service orientation of agent-based control technologies with distributed intelligence. Reflecting the theme of SOHOMA'18: "Digital transformation of manufacturing with agent-based control and service orientation of Internet-scale platforms", the research included focuses on how the digital transformation, as advocated by the "Industry 4.0", "Industrial Internet of Things", "Cyber-Physical Production Systems" and "Cloud Manufacturing" frameworks, improves the efficiency, agility and sustainability of manufacturing processes, products, and services, and how itrelates to the interaction between the physical and informational worlds, which is implemented in the virtualization of products, processes and resources managed as services.
ARTI Reference Architecture - PROSA revisited -- Scientific Discussion: Open Reviews of "ARTI Reference Architecture - PROSA revisited" -- Part I: Cloud Manufacturing: Architectures, Services and Implementation in Production Control -- A distributed approach for machine learning in large scale manufacturing systems -- Cloud-based additive manufacturing as a strategy for product variety: a simulation study -- Architecture for Production Internet -- Integration of a solar panel in power microgrid via Internet of Things -- Intelligent support of requirements management in agile environment -- Industry 4.0 Technologies impacts in the manufacturing and supply chain landscape: an overview -- Part II: Human-centred design for adaptive manufacturing systems -- Human-machine cooperation in self-organized production systems: a point of view -- Architectures for human worker integration in Holonic Manufacturing Systems.
Keywords: Computational intelligence; Manufactures; Artificial intelligence; Computational Intelligence; Machines, Tools, Processes; Artificial Intelligence